O treinamento resistido previne a disfunção mitocondrial no córtex pré-frontal e no músculo vasto lateral de ratas ovariectomizadas - Rossini, Juliana (Universidade Federal de São Carlos, 2016)
Introduction: As we age, human body goes through several important physiological changes, especially in women after menopause, during which estrogen levels are declining, causing changes in mitochondrial function both in skeletal muscle and brain. Menopause is mimicked experimentally by a technique called ovariectomy, that causes some alterations in rats, such as the loss of muscle mass (sarcopenia); however studies have demonstrated that loss of age-related muscle is a different process from strength loss. Whereas the loss of muscle strength is dissociated from this condition, it was renamed as dinapenia. Resistance Training (RT) has beneficial effects on postmenopausal women, but is not well established in the literature the possible effects of RT on mitochondrial function of the cerebral motor cortex and skeletal muscle of ovariectomized rats. Objective: This study aimed to investigate the effects of ovariectomy and resistance training on mitochondrial function (oxygen consumption) in tissue biopsy of the prefrontal cortex and vastus lateralis muscle (VL) in rats. Materials and Methods: were used 40 adult female rats divided into 4 experimental groups (Sham-SED, Sham- TR, OVX-SED and OVX-TR). The ovariectomy was performed at 13 weeks. The Resistance Training (RT) proposed was the climb stairs model, and held for 13 weeks. The masses of the prefrontal cortex, cerebellum, Vastus Lateralis (VL) and Retus Femoralis (RF) were analyzed after sacrifice, which took place 48 hours after the last training session. Oxygen consumption and mitochondrial respiratory parameters were performed on tissue biopsy of the prefrontal cortex and the vastus lateralis (VL) by technique of High Resolution Respirometry (Oroboros®). Results: it was found decreased muscle mass (VL and RF), as well as the cerebellum in OVX-SED group compared to other groups (p <0.05). TR prevented the loss of muscle and cerebelar mass. Mitochondrial oxygen consumption was decreased in OVX-SED group compared to the other experimental groups (p <0.05), effect once again prevented by TR. Conclusion: ovariectomy produced mitochondrial dysfunction in the prefrontal cortex and VL, deleterious effect prevented by RT.
Keywords: Menopausa; Ovariectomia; Disfunção mitocondrial; Sarcopenia; Dinapenia; Menopause; Ovariectomy; Mitochondrial dysfunction; Resistance training; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL